1984
DOI: 10.1083/jcb.98.5.1619
|View full text |Cite
|
Sign up to set email alerts
|

Radioautographic visualization of differences in the pattern of [3H]uridine and [3H]orotic acid incorporation into the RNA of migrating columnar cells in the rat small intestine.

Abstract: The epithelium of rat small intestine was radioautographed to examine whether RNA is synthesized by the salvage pathway as shown after [3H]uridine injection or by the de novo pathway as shown after [3H]orotic acid injection. The two modes of RNA synthesis were thus investigated during the migration of columnar cells from crypt base to villus top, and the rate of synthesis was assessed by counting silver grains over the nucleolus and nucleoplasm at six levels along the duodenal epithelium--that is, in the base,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…It is not always possible to state exactly the relationship between the pattern of mRNA accumulation as measured by in situ hybridisation and the transcription of a gene. In this instance however, the incorporation in RNA precursors into villus cells [44], and the rapid induction of calbindin expression by 1,25, (OH),D, in vitamin-D,-deficient chickens [49], suggest that the pattern of mRNA accumulation measured by this method here and in previous studies [16][17][18][19]491 may reflect a generalised pattern of transcriptional activity within these cells. The clear differences in the levels of each mRNA at a given point during a enterocyte differentiation and maturation are therefore likely to correspond to the level of transcription of that gene during its migration along the crypt-villus axis.…”
Section: Discussionsupporting
confidence: 51%
“…It is not always possible to state exactly the relationship between the pattern of mRNA accumulation as measured by in situ hybridisation and the transcription of a gene. In this instance however, the incorporation in RNA precursors into villus cells [44], and the rapid induction of calbindin expression by 1,25, (OH),D, in vitamin-D,-deficient chickens [49], suggest that the pattern of mRNA accumulation measured by this method here and in previous studies [16][17][18][19]491 may reflect a generalised pattern of transcriptional activity within these cells. The clear differences in the levels of each mRNA at a given point during a enterocyte differentiation and maturation are therefore likely to correspond to the level of transcription of that gene during its migration along the crypt-villus axis.…”
Section: Discussionsupporting
confidence: 51%
“…In this case, a 3 day latent period was already known to precede epithelial denudation (Quastler, 1956). Further evidence in this direction was obtained in a study of RNA synthesis using radioautography (Uddin et al, 1984). This study showed that nucleolar RNA synthesis as well as nucleoplasmic RNA synthesis in the columnar cells become reduced to negligible levels in the upper half of the crypts that is long before reaching the absorptive stage.…”
Section: Roles Of Protein and Rna Synthesismentioning
confidence: 87%
“…1b), but we would today consider these cells to be progenitors committed to the myeloid lineage (proerythroblasts and myeloblasts). Progenitor cells in the crypts of the small intestine have been shown to undergo high levels of nascent transcription (Jao and Salic, 2008; Uddin et al, 1984). Recent reports highlight the importance of increased ribosomal RNA and protein synthesis for the transition between germline stem cells and proliferative progenitors in the Drosophila ovary (Sanchez et al, 2016; Zhang et al, 2014), although hypertranscription was not specifically analyzed.…”
Section: Roles For Hypertranscription In Adult Organ Renewal and Regementioning
confidence: 99%